Utilization of Landsat 8/ETM+ and Google Earth Engine Images for Coastal Identification in Sungai Nibung Village, Kubu Raya Regency, West Kalimantan - Nurdiansyah , Syarif Irwan; Helena, Shifa; Warsidah (Sam Ratulangi University, 2024)
Changes in coastlines cause continuous processes through various processes, both abrasion and coastal accretion, which are caused by sediment movements and coastal currents. This research aims to map changes in the coastline in Sungai Nibung Village using multi-temporal imagery for 2013-2023 from Google Earth Engine (GEE). The benefit of this research is to see changes in the coastline of Sungai Nibung so that coastal area management, including abrasion disaster mitigation, can be carried out appropriately. The method used is a quantitative descriptive method from the results of processed NSM and EPR data from DSAS and the results of Landsat image digitization from GEE. The most extensive abrasion phenomenon results will occur in 2023, namely 64,924 m2 and accretion of 120,886 m2. Coastal changes digitized using ArcGIS showed that the coastline change in 2013 was 0.433 km2, in 2016 it was 0.521 km2, in 2019 it was 0.538 km2 and in 2023 it was 0.649 km2. DSAS analysis shows that almost every stretch of beach in Sungai Nibung has experienced abrasion. Abrasion in Sungai Nibung occurred because there were not many wave breakers and damage to mangrove land. The rate of abrasion in Sungai Nibung over 10 years reached -574.96 m. Keywords: DSAS, EPR, NSM, Google Earth Engine. Abstrak Perubahan garis pantai menyebabkan proses terus menerus melalui berbagai proses baik abrasi maupun akresi pantai yang diakibatkan oleh pergerakan sedimen, arus susur pantai. Penelitian ini bertujuan untuk memetakan perubahan garis pantai di Desa Sungai Nibung menggunakan citra multi temporal tahun 2013-2023 dari Google Earth Engine (GEE). Manfaat penelitian ini untuk melihat perubahan pesisir pantai Desa Sungai Nibung maka pengelolaan kawasan pesisir termasuk di dalamnya mitigasi bencana abrasi dapat dilakukan dengan tepat. Metode yang digunakan adalah metode deskriptif kuantitatif dari hasil olahan data NSM dan EPR dari DSAS dan hasil digitasi Citra Landsat dari GEE. Hasil fenomena abrasi paling luas terjadi di tahun 2023 yaitu 64,924 m2 dan akresi sebesar 120,886 m2. Perubahan pesisir yang digitasi menggunakan ArcGIS diperoleh perubahan garis pantai tahun 2013 sebesar 0,433 km2 , tahun 2016 sebesar 0,521 km2 , tahun 2019 sebesar 0,538 km2 dan tahun 2023 sebesar 0,649 km2. Analisis DSAS hampir di setiap ruas pantai di Desa Sungai Nibung mengalami abrasi. Abrasi di Desa Sungai Nibung terjadi akibat belum banyak pemecah ombak dan rusaknya lahan mangrove. Laju abrasi di Desa Sungai Nibung selama 10 tahun mencapai -574,96 m. Kata Kunci : DSAS, EPR, NSM, Google Earth Engine